INNOVATION IN DIGITAL NURSING DAILY REPORTING THROUGH THE USE OF SPREADSHEETS TO IMPROVE THE QUALITY OF DOCUMENTATION IN INPATIENTS AT PATI ISLAMIC HOSPITAL - Luthfi, Moh. Ady; Yuliani, Feri Catur; Rusyani, Yeni; Abdullah, Akbar Amin (RADJA PUBLIKA, 2025)
Accurate and efficient nursing documentation is crucial for improving the quality of care and patient safety. However, the predominant manual recording practices in the inpatient wards of Pati Islamic Hospital, particularly the Utsman bin Affan ward, create various challenges, such as delayed reporting, recording errors, and limited access to information. This project is to develop and implement a spreadsheet-based digital daily nursing reporting system to improve the quality of documentation. A simple technology development project approach with stages: needs analysis, spreadsheet template design, system implementation, and effectiveness evaluation through observation of filling time and evaluation questionnaires. This spreadsheet-based digital reporting system is able to reduce recording time, increase data accuracy, and receive positive feedback from users, with 92.9% of nurses stating their willingness to use it on an ongoing basis. Digital reporting using spreadsheets has proven to be a practical and effective solution in improving the efficiency and quality of nursing documentation, especially in healthcare facilities with limited technological infrastructure.